حضرت محمد ﷺ کے مسلمان برادرانِ نسبتی کی عسکری سرگرمیاں: Military Activities of Prophet Muhammad’sMuslim Brothers-in-law (Al-Qamar, 2025)
The most beloved Prophet of Allah, Muhammad (SAW). While a great example of love with one’s beloved is to make a promise of Jannatul Firdous for the Ummah of one’s beloved. And making obedience to himself as well as the obedience of his beloved obligatory this is also a great example of love .In the same way, the one who commits love for the Prophet (SAW) will also established and maintain love for the great family of Prophet (SAW) .The companions of Muhammad (SAW) scarified their life, wealth and families in love of Prophet (SAW).Wives of Prophet (SAW) and their every member has importance , including brothers of the Nobel wives of the Holy Prophet (SAW) who are the Brothers-in-law of Muhammad (SAW) .The goal is to shed light on their multiple Activities.
Keywords: Prophet Muhammad (SAW), Brothers-in-law, Military Activities, Companions, Islamic Battles